Toward an Understanding of Aggregate Death Penalty Opinion Change: A Possible Role for Popular Music - Bohm, Robert M.; Surette, Ray (International Journal of Criminology and Sociology, 2013)
Abstract: This study examines the relationship between popular music; specifically, death penalty songs, and aggregate death penalty opinion change utilizing an exploratory time series analysis. An assumption of this study is that the public is made conscious of the death penalty as a salient issue through the popular media, e.g., newspaper stories, magazine articles, movies, television programs, and music. Results of this study support the hypotheses that public consciousness about the death penalty as well as changes in aggregate death penalty opinion are associated with the content of popular media in the form of death penalty songs. As the number of death penalty songs increases in a year, death penalty support decreases two years later.